(untitled) (MATEMATIKA, 2005)
In 1968, Volicko defined the concept of supper-continuity between topological spaces. In this paper supper-continuity is characterised relating to several other well-known variations of continuity, and sufficient and necessary conditions for any of them to imply supper-continuous are also provided. Moreover, many constructions of super-continuity are studied. Keywords: Continuity; supper-closed; characterization; closure. Closure matroid.